Pediatric urology research in 2020: A bibliometric analysis of the top 100 most cited articles. Issue 3 (August 2022) - Ghidini, Filippo; Castagnetti, Marco
Background: Pediatric Urology deals with genitourinary diseases. Present study aimed to collect the top-cited article in Pediatric Urology in order to define the most debated and studied topics. Methods: The journals reported in "Urology & Nephrology" category of the 2019 edition of Journal Citation Reports, together with the most relevant journals of "Transplantation, " "Pediatrics, " and "Surgery" categories, were browsed. The articles of interest in Pediatric Urology with more than 50 citations were collected. A bibliometric analysis was performed to collect the top 100 cited articles. Results: The top-cited articles were published in 27 journals (23%), with a median impact factor of 2.676 (IQR 1.981–5.642). Seventeen of them (63%) belonged to "Urology and Nephrology" category. The median number of citations was 82 (IQR 64–113). The most productive journal, with 23 articles, was "The Journal of Urology." Forty-eight top-cited articles were Guidelines or Reviews of the literature and only four papers were randomized controlled trials. The most relevant topic was "congenital anomalies" with 18 articles. As to minimally invasive surgery, eight studies were identified. All of them dealt with robotic-assisted laparoscopic surgery. Two articles reported the current evidence about transitional care. Conclusions: The top-cited articles were dispersed among journals of different areas. Current scientific literature deal with congenital anomalies, more specifically with obstructive uropathies and hypospadias. In the last decade, one of the most relevant innovation in pediatric urology was the introduction of robotic surgery. Transitional care has become a timely topic.